Tax Refunds and Income Manipulation Evidence from the EITC - Florian Buhlmann; Benjamin Elsner; Andreas Peichl (Institute of Labor Economics (IZA), 2017)
Welfare programs are important for reducing poverty but create incentives for recipients to maximize their income by either reducing labor supply or manipulating taxable income. In this paper, we quantify the extent of such behavioral responses for the Earned Income Tax Credit (EITC) in the US. We exploit that US states can set top-up rates, which means that, at a given point in time, workers with the same income receive different tax refunds in different states. Using event studies as well as a border pair design, we document that a raise in the state-EITC leads to more bunching of self-employed tax filers at the first kink point of the tax schedule. While we document a strong relationship up until the Great Recession in 2007, we find no effect thereafter. These findings point to important behavioral responses to what is the largest welfare program in the US.
Keywords: H20; H24; 330; EITC; tax refunds; income manipulation